2012
DOI: 10.1123/ijspp.7.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Strength Gains: Block Versus Daily Undulating Periodization Weight Training Among Track and Field Athletes

Abstract: Recently, the comparison of “periodized” strength training methods has been a focus of both exercise and sport science. Daily undulating periodization (DUP), using daily alterations in repetitions, has been developed and touted as a superior method of training, while block forms of programming for periodization have been questioned. Therefore, the purpose of this study is to compare block to DUP in Division I track and field athletes. Thirty-one athletes were assigned to either a 10-wk block or DUP training gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 23 publications
4
114
1
4
Order By: Relevance
“…Several studies also observed chronic differences regarding distinct methods of periodization (Simão et al, 2012;Bartolomei et al, 2014;de Lima et al, 2012;Painter et al, 2012). The previous investigations differ from our experiment mainly for the population and RE methodology applied.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Several studies also observed chronic differences regarding distinct methods of periodization (Simão et al, 2012;Bartolomei et al, 2014;de Lima et al, 2012;Painter et al, 2012). The previous investigations differ from our experiment mainly for the population and RE methodology applied.…”
Section: Discussioncontrasting
confidence: 53%
“…This method was applied to RE since the 1950s and has grown in popularity since then (Simão et al, 2012). It is well reported in the scientific literature that strength gains were higher when periodization methods are implemented compared to different or non-periodization methods (Baker et al, 1994;Bartolomei et al, 2014;de Lima et al, 2012;Miranda et al, 2011;Painter et al, 2012;Peterson et al, 2008;Prestes et al, 2009a;Prestes et al, 2009b;Rhea et al, 2002;Rhea et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groups followed a block-periodized model with heavy and light days within each microcycle to manage fatigue. 12,13 Load for squat and partial-squat was calculated using percentage of pre-intervention 1-RM. All training sessions were supervised to ensure correct technique and safety.…”
Section: Trainingmentioning
confidence: 99%
“…Long-term, periodized resistance exercise training produces increased skeletal muscle size and, ultimately, force-generating capacity [1][2][3]. Sports nutrition scientists have attempted to increase training-induced gains through a number of protocols, which generally attempt to augment and/or speed skeletal muscle regeneration.…”
Section: Introductionmentioning
confidence: 99%